Strong metal-support interaction promoted via constructing biocarbon membrane for enhanced CO preferential oxidation activity of Rh/CaCO3@biocarbon. (30th August 2019) - Ding, Junfang; Li, Liping; Wang, Ye; Xu, Xianzhe; Chen, Shaoqing; Wang, Xiyang; Li, Huixia; Zhao, Shuaiqiang; Li, Guangshe
Abstract: Precious metal nanoparticles, widely used as heterogeneous catalysts, are easy to aggregate and deactivate, restricting their applications in many important catalytic fields like preferential CO oxidation (CO-PROX) in H2 -rich stream. In this work, well dispersed Rh nanoclusters anchored on CaCO3 @biocarbon derived from waste eggshell (ESMC) were synthesized through a step carbonization and incipient wetness impregnation process. The obtained catalysts exhibited 3D macroporous architecture, which is favorable for exposure of more nucleation sites of precious metal Rh, thus minimizing the aggregation of Rh particles. Furthermore, a thick carbon shell attached to eggshells, with interesting electronic structure and surface chemistry, efficiently transfers electrons between Rh and biocarbon@CaCO3 support, and enhances the interaction between Rh NPs and support. Both effects synergistically allow Rh/ESMC to equip more active adsorption sites-asymmetric Rh(CO)2 gem-dicarbonyl, thus greatly promoting the catalytic performance of Rh/ESMC in CO-PROX (operation temperature window: 140–240 °C). The present finding offers an environmentally friendly approach to fabricate well dispersed Rh nanoclusters catalysts, and it can be extended to rationally design other supported metal nanoparticle catalysts. Graphical abstract: Image 1 Highlights: Well dispersed Rh nanoclusters anchored on waste eggshell were synthesized. The thick carbon layer can efficiently prevent the agglomeration of Rh nanoclusters. The strong metal–support interaction exists between Rh NPs and CaCO3 @biocarbon. High performance and stability of catalysts exhibited for CO-PROX reaction.